World rice market update: more trade, better weather, lower prices - Dawe, David; Pede, Valerien Olivier; Antonio, Ronald Jeremy (International Rice Research Institute, 2024)
Good news: the recent developments in the global rice trading environment and improved weather conditions have lowered world market prices. As these factors lead to lower domestic prices, consumers will find it easier to afford a healthy diet.